STUDI TEORITIS MATERIAL KATODA BATERAI ION LITIUM LiFePO4 BERDASARKAN KALKULASI TEORI FUNGSIONAL KERAPATAN - Lalu Suhaimi; Syamsul Bahtiar; Muhammad Hilmy Alfaruqi (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
To fully utilize the intermittent renewable energy resources, energy storage applications such as lithium-ion batteries (LIBs) become very critical. Among LIBs components, cathode part is very important. LiFePO4 material is among the cathode material which has gained significant attention owing to its environmentally friendly and low-cost features compared to Co- or Ni-based cathodes. In this study, we present a theoretical investigation of LiFePO4 material using density functional theory calculations. We optimized LiFePO4 as well as FePO4 structures. Li ion intercalation potential into the structure was also calculated. In addition, the electronic structure of the material was also studied. The present study may provide an insight for further investigation of cathode materials for LIB applications.